2001
DOI: 10.1002/cne.1331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the central nervous system innervation of the rat spleen using viral transneuronal tracing

Abstract: Splenic immune function is modulated by sympathetic innervation, which in turn is controlled by inputs from supraspinal regions. In the present study, the characterization of central circuits involved in the control of splenic function was accomplished by injecting pseudorabies virus (PRV), a retrograde transynaptic tracer, into the spleen and conducting a temporal analysis of the progression of the infection from 60 hours to 110 hours postinoculation. In addition, central noradrenergic cell groups involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
124
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 205 publications
(143 citation statements)
references
References 90 publications
(123 reference statements)
15
124
1
2
Order By: Relevance
“…5 G and H), indicating that nerve terminals found in juxtaposition to TNF-producing macrophages are catecholaminergic. In agreement with studies that indicate lack of vagus innervation of the spleen (14,16,17), staining of spleen sections with antibodies against choline acetyltransferase or vesicular acetylcholine transporter, markers of cholinergic neurons, failed to reveal cholinergic nerve fibers (data not shown). Together, these results indicate that the nerve fibers supplying the TNF-secreting macrophages are catecholaminergic, not cholinergic.…”
Section: Nerve Terminals In the Spleen Are Found Adjacent To Tnf-prodsupporting
confidence: 88%
See 2 more Smart Citations
“…5 G and H), indicating that nerve terminals found in juxtaposition to TNF-producing macrophages are catecholaminergic. In agreement with studies that indicate lack of vagus innervation of the spleen (14,16,17), staining of spleen sections with antibodies against choline acetyltransferase or vesicular acetylcholine transporter, markers of cholinergic neurons, failed to reveal cholinergic nerve fibers (data not shown). Together, these results indicate that the nerve fibers supplying the TNF-secreting macrophages are catecholaminergic, not cholinergic.…”
Section: Nerve Terminals In the Spleen Are Found Adjacent To Tnf-prodsupporting
confidence: 88%
“…5 C and D). Previous studies indicate that innervation of the spleen is supplied by the splenic nerve, which is comprised principally of catecholaminergic fibers originating in the ganglia of the celiac-superior mesenteric plexus (15)(16)(17). Spleen tissue treated with glyoxylic acid, a standard procedure to stain catecholamines (26), revealed an extensive nerve fiber network that followed the same distribution as that of synaptophysin ( Fig.…”
Section: Nerve Terminals In the Spleen Are Found Adjacent To Tnf-prodmentioning
confidence: 95%
See 1 more Smart Citation
“…At longer survival times, virus labeling was detected in premotor sympathetic brain nuclei in the brain stem, pons and hypothalamus. While the central pattern of transneuronal labeling was comparable to what has been reported for the thymus and spleen (Cano et al, 2001;Trotter et al, 2007), the amount of central labeling of PRV infected neurons was very limited and likely was due to the high and neurotoxic doses of PRV required to initiate transneuronal transport from bone marrow. However, their results establish the origin of sympathetic neural input to bone marrow, and importantly, dual transneuronal labeling with two isogenic, but histochemically distinguishable, forms of PRV allowed a comparison between bone marrow versus the overlying skeletal muscles.…”
Section: Innervation Of Bone Marrowsupporting
confidence: 76%
“…Similarly, immunohistochemical studies for vesicular acetylcholine transporter, a highly specific marker for cholinergic neurons and fibers, indicated their complete absence in lymphoid tissue (Schafer et al, 1998). Finally, a transneuronal study of the innervation of the spleen with PRV has verfied this conclusion (Cano et al, 2001) and demonstrated that sympathetic preganglionic neurons that innervate the spleen arise from the T1-T12 region of the thoracic spinal cord. Longer survival times identified sympathetic premotor brain nuclei projecting either directly or indirectly to the spinal sympathetic preganglionic neurons, and again consisted of many of the same nuclei in the brainstem, pons and hypothalamus that are activated by immune stimuli ( Wan et al, 1994).…”
Section: Innervation Of the Spleenmentioning
confidence: 88%